2013
DOI: 10.1007/s10495-012-0793-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of retinal endothelial cell apoptosis through activation of the IGFBP-3 receptor

Abstract: The goal of this study was to investigate whether insulin-like growth factor binding protein-3 receptor (IGFBP-3 receptor) is required for IGFBP-3 to inhibit retinal endothelial cell (REC) apoptosis. REC were grown in normal glucose (5 mM) or high glucose medium (25 mM) for 3 days. Once cells reached confluence, they were transfected with an endothelial- specific IGFBP-3 plasmid DNA (non-IGF binding; IGFBP-3 NB) at 1 μg/ml for 24 h. Cell proteins were extracted and analyzed for IGFBP-3 receptor expression by W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…By using a mutant form of IGFBP-3 that cannot bind IGF-1, it is possible to observe IGF-1 independent actions of IGFBP-3. Under these conditions (in our case, transfection of REC with mutant non-binding, IGFBP-3 NB plasmid), we found that overexpression of IGFBP-3 NB led to a reduction in TNF-α levels and a subsequent reduction in REC apoptosis (Zhang et al, 2013a,b). The studies described here also use IGFBP-3 NB plasmid and thus, all the findings contained in this report are limited to actions of IGFBP-3 that are independent of IGF-1 binding.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…By using a mutant form of IGFBP-3 that cannot bind IGF-1, it is possible to observe IGF-1 independent actions of IGFBP-3. Under these conditions (in our case, transfection of REC with mutant non-binding, IGFBP-3 NB plasmid), we found that overexpression of IGFBP-3 NB led to a reduction in TNF-α levels and a subsequent reduction in REC apoptosis (Zhang et al, 2013a,b). The studies described here also use IGFBP-3 NB plasmid and thus, all the findings contained in this report are limited to actions of IGFBP-3 that are independent of IGF-1 binding.…”
Section: Introductionmentioning
confidence: 67%
“…Previous studies have demonstrated that this model system demonstrates many features of retinal endothelial cells in vivo from diabetic animals (Zhang et al, 2012, 2013a,b). These common features, including high levels of TNF-α as well as vascular cell death, are causative in the development of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A subsequent study showed that IGFBP3 increased tube formation and angiogenesis-related gene expression including VEGF, MT1-MMP and MMP2, as well as increasing MMP2, and MMP9 activation (Granata et al 2007). Incubation in high glucose increased death of primary human retinal microvascular endothelial cells and IGFBP3 inhibited this effect via the LRP1/TGFB receptor (Zhang et al 2013a), which has been reported to mediate IGF-independent actions of this IGFBP (Huang et al 2003). The anti-apoptotic effect of IGFBP3 was associated with increased AKT phosphorylation and Bcl-xL levels while cytochrome c, BAX and cleaved caspase 3 were decreased in these cells.…”
Section: Insulin-like Growth Factor-binding Proteinsmentioning
confidence: 96%
“…Increased levels of IGFBP-3 in the knockdown mice can significantly reduce TNFα levels through activation of the Jun pathway (Zhang et al, in revision). Additionally, Compound 49b-induced increases in IGFBP-3 levels after ocular blast likely reduced pro-apoptotic factors, Bax, cytochrome C, and cleaved caspase 3, through activation of its receptor [12]. Thus, we conclude that Compound 49b is effective in protecting the retina against blast-induced injury through increasing IGFBP-3 levels, as well as reducing TNFα signaling.…”
Section: 0 Discussionmentioning
confidence: 90%